Caravaggio: The Complete Works - Caravaggio, Michelangelo Merisi da 1573-1610; Schütze, Sebastian (Cologne Taschen, 2017)
This title offers a comprehensive examination of the whole of Caravaggio's œuvre with a catalogue raisonée of his works. Five introductory chapters analyse his artistic career from his training in Lombard Milan and his triumphal rise in papal Rome up to his dramatic final years in Naples, Malta and Sicily.
Images of Caravaggio : historical and historiographical perspectives -- Lombard beginnings, 1571-1592 -- The path to artistic autonomy, 1592-1599 -- The large religious works in Rome, 1599-1606 -- The late œuvre in Southern Italy : Naples-Malta-Sicily, 1606-1610 -- Reflections and refractions -- Catalogue of paintings.
Includes bibliographical references (pages 484-504) and index.
Originally published in 2009
Keywords: 17th Century (1601-1700); Fine art; Baroque; Italy